The antimicrobial activity of theobromine against cariogenic microbes: an in vitro pilot study - Ismaeel H. Rafiq; Naile Dame-Teixeira; Thuy Do (Nature Publishing Group, 2024)
Abstract Objective This pilot study aimed to compare the antimicrobial effect of theobromine, sodium fluoride, and a theobromine-sodium fluoride combination against the following caries-associated bacteria: Streptococcus mutans and Actinomyces naeslundii. Methodology Antimicrobial susceptibility was tested via the broth microdilution method, with suspensions cultured on each microbe's respective selective media. Shapiro-Wilk's was completed and all the data showed normality (p > 0.05), and One-way ANOVA was applied to infer the significant differences in the viable counts between the groups. Results All experimental conditions for both S. mutans and A. naeslundii groups resulted in a significantly lower bacterial abundance in comparison to the control medium, without any active antimicrobial agent (p < 0.001). There was no significant difference in viable count between the theobromine, fluoride, or combination groups against either microbe (p > 0.05). Conclusion Theobromine's antimicrobial activity against S. mutans and A. naeslundii was found similar to that of fluoride, whether used independently or in combination. Further testing of theobromine is necessary to assess its role as an alternative anticaries agent.